The Effect of Expository Learning Strategies on Student Responses in PAK Learning - Angga Mahyuda Sinaga; Zefanya Adriani Fitura Sirait; Damayanti Nababan (Indonesian Journal of Advanced Research, 2023)
Teaching strategy is one of the elements that must be understood by a teacher. Learning strategies are developed according to a certain approach. Learning strategies consist of all academic components and procedures that help students achieve certain learning goals. Teaching strategies can also be interpreted as models of teaching activities that are chosen and used by teachers depending on the characteristics of students, school conditions, the environment and the specific learning objectives that are formulated. In the world of education, a teacher must have used an expository strategy, especially an PAK teacher who used an expository learning strategy in the lecture method delivered to students. Moreover, this strategy uses the lecture method, such as for example how to teach Jesus who uses the lecture method, where his sermon is written in Matthew 5-7. The expository strategy is very effectively used in PAK learning because PAK learning contains many elements of religious history which the teacher conveys to students in the form of lectures.